PERCEPTION OF PRE-SERVICE TEACHERS WITH METACOGNITIVE STRATEGY TO INCREASE STUDENTS ABILITY IN LISTENING COMPREHENSION - Jaelani, Alan; Rusydi, Supyan; Saputra, Yoga Adi (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Listening comprehension should emphasize the process, students focus during learning to build their knowledge through a series of speakers so that learning becomes meaningful to students. Listening skills can be classified into two parts, basic skills and integrated skills. In principle, basic skills and integrated skills have in common in terms of formulating problems, collecting data and proposing problem solving solutions. Metacognitive refers to higher-order thinking that involves active control in the cognitive process of learning in solving a problem. Activities such as analyzing English speakers, increasing understanding, and evaluating listening comprehension are natural metacognitive. Metacognitive is the ability to think in which the object of thinking is the thought process that occurs in yourself. In the context of learning, students know how to learn, know their abilities and learning modalities, and know the best learning strategies for effective learning. Metacognitive as a form of ability to look at oneself so that what he does can be controlled optimally. Students with metacognitive knowledge are aware of the advantages and limitations of learning. This means that when students know their mistakes, they realize to admit that they are wrong, and try to correct it. For this reason, pre-service teachers need to try to train students to have metacognitive abilities and bring them up so that they can ultimately improve their listening comprehension. Before that, it is necessary to know how pre-service teachers 'perceptions of metacognitive strategies are to improve students' abilities in lisetening comperhension. This article will focus on the understanding and perceptions of pre-service teachers of metacognitive strategies. This study will examine seven respondents from 5k semester students of English Language Education Program at Universitas Ibn Khaldun. Research conducted using quantitative and qualitative, by giving questionnaires and conducting interviews which then proceed to the analysis of the data. The results are intended that the majority of pre-service teachers still do not fully understand metacognitive strategies.Â